Analysis Proximate, HCN , Antioxidant Compounds And Antioxidant Activities Of Potential Extract As Antiatherosclerosis - Edy Soesanto (Media Keperawatan Indonesia, 2018)
Bamboo shoots are plants that are very easy to find in Indonesia and can grow anywhere, economically bamboo shoots are very cheap and have been used by people in the world as foodstuffs since time immemorial. Aside from being a bamboo shoot food, it also has functions related to hypocholesterolemia, so it can be used as an alternative non-pharmacological treatment or as a traditional medicine derived from medicinal plants (Complementary Therapy). This study aims to determine the levels of protein, fat, water, ash, carbohydrates, HCN, phenols, flavonoids, vitamin E from bamboo shoots and their antioxidant activity. Bamboo shoots used include: yellow bamboo shoots, wulung, green, apus, and betung. Bamboo shoots are thinly sliced and dried in an oven of 80 0C for 24 hours and smoothed to get bamboo shoot powder and then extracted using 70% ethanol which will be analyzed for chemical compounds using the SNI 01-2891-1992 method for proximate test, HCN test using AOAC, while testing phenol, flavonoids, and vitamin E compounds using a spectrophotometer, testing antioxidant activity using DPPH method. The results of the proximate test analysis of 5 bamboo shoot extract samples showed that yellow bamboo shoots contained at most 0.632% fat, 4.474% water, 0.878 gr ash, 29.78% carbohydrates and 4.12 gr crude fiber. The highest protein content test of 0.41% was found in Apus bamboo shoots extract and the highest HCN content was also in Apus bamboo shoot extract 3.98 mg / 100gr. The highest content of Vitamin E is found in Apus bamboo shoots extract which is 0.3284%, the highest total flavonoid content is found in green bamboo shoots extract that is equal to 0.02778%, the most phenolic content in bamboo shoots extract is apus bamboo shoots extract of 4.4352% and the test results Apus bamboo antioxidant activity is more active as an antioxidant than other bamboo shoots which is 171.15 µg / mL with IC 50 value. This shows that Apus bamboo shoots extract is relatively safe for consumption and has good antioxidant potential and can be used as traditional medicine which comes from medicinal plants (Complementary Therapy)